Pulmonary nocardiosis caused by Nocardia exalbida mimicking lung cancer. Issue 7 (1st July 2019) - Miyaoka, Chika; Nakamoto, Keitaro; Shirai, Tatsuya; Miyamoto, Maki; Sasaki, Yuka; Ohta, Ken
Abstract : Nocardiosis is an uncommon infection caused by Nocardia species, but it can often occur in immunocompromised patients. As computed tomography (CT) findings of pulmonary nocardiosis, consolidation, masses, and nodules are often found, but lymph node enlargement is infrequent. Nocardia exalbida was first isolated in 2006, and there are still few reports on this microorganism. We report a case of pulmonary nocardiosis caused by N. exalbida presenting as a mass and lymph node enlargement that mimicked lung cancer. A 76‐year‐old man was referred and admitted to our hospital because of persistent cough, sputum production, and chest discomfort. Chest CT showed a mass in the superior segment of the left upper lobe and mediastinal lymph node enlargement. After we performed bronchoscopies, Nocardia species was isolated in a cultured specimen and identified as N. exalbida . This case required differentiation from lung cancer and was difficult to diagnose. Abstract : Nocardiosis is an uncommon infection caused by Nocardia species that can often occur, mostly as pulmonary lesions, in immunocompromised patients with organ transplantation and cancer. Consolidation, masses, and nodules are frequent computed tomography (CT) findings, but lymph node enlargement is rare. We report a rare case of pulmonary nocardiosis caused by Nocardia exalbida with CT findings of a mass and lymph node enlargement, requiring differentiation from lung cancer and that was difficult to diagnose.